Efficient Preparation of Graphene/Zinc Oxide Nanocomposites / Marlinda Binti Ab Rahman - Ab Rahman, Marlinda (2013)
In the present work, the objective is to prepare graphene-based nanocomposites which aimed at producing graphene in large scale with inorganic materials (zinc oxide, ZnO) homogeneously distributed on the graphene planes. The graphene/zinc oxide nanocomposites were efficiently prepared by a simple hydrothermal method. Two different types of graphene starting materials were used in the synthesis process: graphene oxide (GO) and functionalized graphene oxide (FGO). These two materials resulted in nanocomposite with different morphologies of ZnO decorated on graphene sheets. The GO was prepared by simplified Hummer’s method, followed by mixing with zinc seed precursor (zinc acetate dehydrate (Zn(CH3COO)2.2H2O)) under reflux stirring method. The reduction of zinc oxide nanorod-like on the surface of GO sheets was finally obtained by hydrothermal method. The GO is heavily oxygenated graphene with carbonyl, hydroxyl and epoxy groups on the basal plane and also the carboxylic groups attached to the edges of carbon sheets. These functional groups served as an anchor and at the same time provided a suitable condition for the formation of ZnO nanorods attached to the surfaces and edges of the GO sheets. The graphene/ZnO nanoflower-like was prepared by using the same method by replacing GO with FGO. In this case, the FGO appeared as substrate for the in situ formation of nanoflower-like ZnO. The FGO also served as stabilizer and at once reacted as reducing agent for zinc oxide nanoflower under alkaline medium. These results indicate that the graphene starting materials served as an important controlling factor for the morphology of ZnO decorated on graphene surface.